2020
DOI: 10.1101/2020.02.03.932079
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Triacylglycerol synthesis enhances macrophage inflammatory function

Abstract: Macrophages are integral to most tissues. Foam cells, macrophages with lipid droplets (LDs) which are stores of triacylglycerols (TGs) and cholesterol esters (CEs), are found in various disease states 1 . LDs can act as energy stores since TG lipolysis releases fatty acids (FAs) for mitochondrial oxidation (FAO), a process that relies on long-chain FA conversion into acylcarnitines by the enzyme Cpt1a 2 . However, in macrophages, proinflammatory signals result in diminished FAO and increased TG synthesis with … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 48 publications
9
39
0
Order By: Relevance
“…Importantly, eicosanoid production and action seems to be regulated at the transcript level upon inhibiting triglyceride synthesis. This is in agreement with previous studies in murine bone marrow derived macrophages where inhibition of DGAT1 in M1 polarized macrophages led to decrease in levels of prostaglandins via expression of the gene ptges (Castoldi et al, 2020). Previously, prostaglandin production by IFNγ polarized, Mtb infected BMDMs was also shown to be partially triglyceride dependent (Knight et al, 2018).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Importantly, eicosanoid production and action seems to be regulated at the transcript level upon inhibiting triglyceride synthesis. This is in agreement with previous studies in murine bone marrow derived macrophages where inhibition of DGAT1 in M1 polarized macrophages led to decrease in levels of prostaglandins via expression of the gene ptges (Castoldi et al, 2020). Previously, prostaglandin production by IFNγ polarized, Mtb infected BMDMs was also shown to be partially triglyceride dependent (Knight et al, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have demonstrated that in both human and mouse macrophages, triglyceride synthesis by the enzyme DGAT1 enhances the pro-inflammatory response to both M. tuberculosis and LPS (Castoldi et al, 2020;Jaisinghani et al, 2018). However, the inflammatory responses in vivo in a granulomatous disease could be the sum total of contribution from various cell types and signals.…”
Section: Dgat1 Inhibition Alters the Pro-inflammatory Cytokine Profilementioning
confidence: 99%
See 1 more Smart Citation
“…It emphasized that although glucose carbon enters mitochondria and is used to produce citrate, a break occurs after this point in the TCA cycle, at least in part due to reduced expression of isocitrate dehydrogenase (Idh), that substantially diminishes the production of α-ketoglutarate (α-KG) from glucose carbon ( Figure 1). This favors the accumulation and export of citrate for FAS, which allows membrane synthesis, 10 as well as lipid droplet development that, if inhibited, has marked effects in macrophage inflammatory potential 32 (Figure 1). Moreover, the parallel induction of expression of aconitate decarboxylase 1 (encoded by Acod1, also referred to as Irg1) allows the use of (iso) citrate carbon, via aconitate, for high output synthesis of the metabolite itaconate (Figure 1).…”
Section: A Broken Tca Cyclementioning
confidence: 99%
“…29 Others have demonstrated that lipid droplets can act as reservoirs for precursor molecules required for pro-inflammatory mediator synthesis, and therefore increased macrophage triglyceride storage can heighten inflammatory response. [30][31][32] Support for the lipid-mediator pool hypothesis comes from data obtained from macrophages lacking Hypoxia Inducible Lipid Droplet Associated (HILPDA) protein, a potent endogenous inhibitor of ATGL. 33 Hilpda-deficient macrophages cannot store triglycerides, leading to impaired prostaglandin E2 production.…”
Section: Introductionmentioning
confidence: 99%